Intelligent control electromagnetic actuated continuously variable transmission system for passenger car - Rahman, Mohammed Ataur; Sharif, Sazzad; Mohiuddin, A. K. M.; Ismail, Ahmad Faris; Ihsan, Sany Izan (IOP Publishing, 2017)
Continuously variable transmission (CVT) system transmits the engine /battery power to the car driving wheel smoothly and efficiently. Cars with CVT produces some noise and slow acceleration to meet the car power demand on initial start-ups and slow speed. The car noise is produced as a result of CVT adjustment the engine speed with the hydraulic pressure. The current CVT problems incurred due to the slow response of hydraulic pressure and CVT fluid viscosity due to the development of heat.The aim of this study is to develop electromagnetic actuated CVT (EMA-CVT) with intelligent switching controlling system (ICS). The experimental results of ¼ scale EMA shows that it make the acceleration time of the car in 3.5-5 sec which is 40% less than the hydraulic CVT in the market. The EMA develops the electromagnetic force in the ranged of 350 –1200 N for the supply current in the range of 10-15 amp. This study introduced fuzzy intelligent system (FIS) to predict the EMA system dynamic behaviour in order to identify the current control for the EMA actuation during operation of the CVT. It is expecting that the up scale EMA-CVT would reduce the 75% of vehicle power transmission loss by accelerating vehicle in 5 sec and save the IC engine power consumption about 20% which will makes the vehicle energy efficient (EEV) and reduction of green house gas reduction.